ACADEMIC HARDINESS, SKILLS, AND PSYCHOLOGICAL WELL-BEING ON NEW STUDENT - Wardani, Ria (Faculty of Psychology, Diponegoro University, 2020)
This study aims to determine the academic hardiness of new students and use a model that integrates transformational coping, social support, and psychological well-being. As individuals undergoing a period of educational transition, new students need to adapt to the requirements and academic tasks that are different from schooling and insist on them to demonstrate their strong persistence personalities and develop their psychological well-being. This study uses a non-experimental cross-sectional research design. A total of 237 participants filled out the academic hardiness, skills, and psychological well-being questionnaire, and the data were analyzed with SEM version 8.80. The test results show that academic hardiness plays a direct role in developing participant's psychological well-being. Even though academic hardiness plays a role in developing transformational coping and social support skills, both skills do not play a role in fostering psychological well-being. These results indicate that commitment - control - and challenges that reveal participants' ability to adapt to the new academic demands can improve their individual ability to demonstrate their fully functioning self or fully functioning person in completing academic demands and tolerating pressures. However, a similar role does not find transformational coping skills and social support skills as the product of academic hardiness. The skill level does not determine the development of the participant's psychological well-being.